2011
DOI: 10.1002/pola.24513
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of random PET‐co‐PTTs and some related copolyesters by entropically‐driven ring‐opening polymerizations and by melt blending: Thermal properties and crystallinity

Abstract: A library of random poly(ethylene terephthalate) (PET), poly(trimethylene terephthalate) (PTT), and seven PET-PTT copolymers has been prepared in a high throughput manner by entropically-driven ring-opening polymerizations of the corresponding macrocyclic oligomers. The products have been investigated by differential scanning calorimetry and wide angle X-ray diffraction. They show that the 50:50 copolymer displays a crystalline phase. The same phase can be formed by in situ transesterification when a 50:50 mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The possibility of transesterification reactions is in agreement with the observed increase in the polydispersion index (Table IV). 20–22…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of transesterification reactions is in agreement with the observed increase in the polydispersion index (Table IV). 20–22…”
Section: Resultsmentioning
confidence: 99%
“…Conzatti et al [16] showed that at relative short blending time, the blend forms a block copolymer, while, with increasing the time, the block lengths shortened till to form a random copolymer. In the light of these results, the conditions adopted to prepare the C1 sample should produce a copolymer with marked block features.…”
Section: Resultsmentioning
confidence: 98%
“…Previous works demonstrated that mechanical and thermal conditions adopted in preparing the PET/PTT 50/50 blend induced transesterification reactions between the polyesters to produce a new molecular features based on PET/ PTT copolymer. The ability of the generated copolymer to form crystal is affected by the length of the blocks and by the distribution of the crystallisable segments of different lengths [15,16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations